Analyzing the Effects of Covid-19 Pandemic on the Financial Performance of Turkish Listed Companies on Borsa Istanbul using the Entropy-based Grey Relational Analysis - Özcan, Sami; Serçemeli, Murat; Çelik, Ali Kemal (International Journal of Economics and Financial Issues, 2024)
The purpose of this study is to use financial performance indicators to reveal how Covid-19 affects different sectors of companies operating in Turkey compared to their financial performance in previous years. The financial performance of 210 companies operating in manufacturing, construction, and technology sectors was explored through ratio analysis, using four main and 15 sub-financial performance ratios. The effects of Covid-19 on their financial performance were investigated with the entropy-based grey relational analysis technique. The results of the study show that Covid-19 positively affected the manufacturing and technology sectors in Turkey, whereas it negatively affected the construction sector. In light of the results, this study contributes to manufacturing, construction, and technology companies to take measures against possible global crises that may arise in the future based on the effects of the Covid-19 period.